Talent shortages and talent surpluses in the mining industry in South America - Gallegos Monteagudo, Armando (2011)
A study of talent shortages and talent surpluses in the mining industry in various South American nations was conducted. GĚRENS has completed a study of the growth in the demand for professionals in the mining industry in Peru. It found that contractors, consulting companies, and equipment suppliers have the highest volatility, ranging from very high rates of demand in optimistic scenarios to significant decreases under pessimistic ones. Quality of education in mining, geology and metallurgy is a major issue for the South American mining industry. If quality revamping becomes successful, given the high and increasing enrolment in mining and geology schools, Peru, Chile and other South American countries could not only satisfy their internal demand for talent but become significant exporters of talent.